1997
DOI: 10.1007/s002800050690
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to camptothecin of human breast carcinoma and normal endothelial cells

Abstract: The results suggest that cell cycle regulation plays an important role in determining the effect of CPT on malignant and normal cells. The possible mechanisms explaining the sensitivities of the two cellular compartments to the action of CPT are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Camptothecin also shows close toxicity to both KB cells (IC 50 = 65 nmol/l) and IMR90 cells (IC 50 = 100 nmol/l). The IC 50 values from our pilot study are similar to those in the literature reports [23][24][25]. However, bortezomib inhibited the cell proliferation, with IC 50 levels of 1.5 and 100 nmol/l for KB and IMR90, respectively.…”
Section: Anticancer Study Of Individual Drugssupporting
confidence: 88%
“…Camptothecin also shows close toxicity to both KB cells (IC 50 = 65 nmol/l) and IMR90 cells (IC 50 = 100 nmol/l). The IC 50 values from our pilot study are similar to those in the literature reports [23][24][25]. However, bortezomib inhibited the cell proliferation, with IC 50 levels of 1.5 and 100 nmol/l for KB and IMR90, respectively.…”
Section: Anticancer Study Of Individual Drugssupporting
confidence: 88%
“…Ellipticine and camptothecin were previously tested in other cell lines with the use of other methodologies. For these studies, CC 50 values of 0.3 to 3 M for ellipticine (13,42) and 7 to 330 nM for camptothecin (7,21) were reported. Although there are variations in toxicity among the cell lines and the methods chosen in these studies, these CC 50 values basically agree with the results reported in this study, pointing out the validity of the trypan blue exclusion method employed in the current study to evaluate cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by our laboratories and others, for example, showed that p53 mutations in human tumor cells were correlated with decreased sensitivity to DNA damaging agents [3][4][5][6]. Hence an improved understanding of the relationship between p53 and chemosensitivity may lay the groundwork for new cancer therapies.…”
Section: Introductionmentioning
confidence: 99%